Communication Discourse on Population Policy Dynamics and Development in Nigeria - Ibrahim Abdulkadir; Yoserizal saragih; Muhammad Ridwan (Matondang Journal, 2026)
This paper examines the dynamics of population policy and its implications for national development in Nigeria from a communication perspective. Nigeria’s rapid population growth, youthful demographic structure, and persistent socio-economic challenges have made population policy a critical development concern. The paper discusses how communication processes shape the formulation, interpretation, and implementation of population policies, as well as public understanding and acceptance of policy objectives such as fertility regulation, reproductive health, family planning, and sustainable development. Drawing on policy documents, existing literature, and communication-for-development frameworks, the paper analyses the roles of government agencies, the media, civil society organisations, religious and traditional institutions, and development partners in population policy discourse. The paper argues that the technocrat elite accepted the policy largely on its own merits, national leaders negotiated the policy by it facilitated state-society relations, deflected blame for economic woes, and representatives of social and religious groups rejected the policy. Many wonder why Nigeria, a country in which population was highly politicized, adopted a policy aiming to limit fertility. Further, some groups tend to see prestige and strength in large numbers and suspect that western warnings about high growth rates are an imperialist conspiracy to keep them undeveloped. The paper points that population policy success in Nigeria is not only a matter of demographic targets but also of effective, culturally sensitive, and inclusive communication strategies that align population goals with citizens’ lived realities. It concludes that strengthening evidence-based communication, media advocacy, and stakeholder collaboration is essential for aligning population policy with sustainable development objectives in Nigeria.